Optimization of N-benzyl-5-nitrofuran-2-carboxamide as an antitubercular agent. Issue 4 (15th February 2019) - Gallardo-Macias, Ricardo; Kumar, Pradeep; Jaskowski, Mark; Richmann, Todd; Shrestha, Riju; Russo, Riccardo; Singleton, Eric; Zimmerman, Matthew D.; Ho, Hsin Pin; Dartois, Véronique; Connell, Nancy; Alland, David; et al.
Graphical abstract: Abstract: The optimization campaign for a nitrofuran antitubercular hit ( N -benzyl-5-nitrofuran-2-carboxamide;JSF-3449 ) led to the design, synthesis, and biological profiling of a family of analogs. These compounds exhibited potent in vitro antitubercular activity (MIC = 0.019–0.20 μM) against the Mycobacterium tuberculosis H37Rv strain and low in vitro cytotoxicity (CC50  = 40–>120 μM) towards Vero cells. Significant improvements in mouse liver microsomal stability and mouse pharmacokinetic profile were realized by introduction of an α, α-dimethylbenzyl moiety. Among these compounds, JSF-4088 is highlighted due to its in vitro antitubercular potency (MIC = 0.019 μM) and Vero cell cytotoxicity (CC50  > 120 μM). The findings suggest a rationale for the continued evolution of this promising series of antitubercular small molecules.